Cloud Based Neo-Natal Health Care Monitoring From NICU-An Application Of Internet Of Medical Things(IoMT) - Nitesh K C, N MahideepSai, A Sandeep,Tanuja G,Srinivasulu A,Anughna N (International Journal of Advanced Science and Technology, 2020)
The paper aims to achieve the goals in the area of neonatal ICUs (NICU). In case of premature, Low birth weight (less than 1Kg) babies, we have to take care of infants, we have proposed an Intensive Care Unit which will monitor its health and take care of the baby with alert systems. In this system we are monitoring Body temperature, incubator temperature and pulse. Additional to this we are introducing pram motion.